Effects of methyl jasmonate elicitation on growth and lutein content in microshoot cultures of Ruta angustifolia (L.) Pers - Mohd. Hassan, Norazian; Othman, Rashidi; Sulaiman, Shaida Fariza; Syed Salim, Sharifah Maizurah; Mohd Zaifuddin, Fatimah Azzahra; Ramya, Razanah (2015)
Lutein is one of the macular pigments which protects the underlying photoreceptor cell layer of the retina from light-induced oxidative damage. The carotenoid pigment has been detected in the intact plant of Ruta angustifolia. In this study the effects of methyl jasmonate (MeJa) elicitation on growth and lutein content in microshoot cultures of R. angustifolia were investigated. The green microshoot cultures which were successfully induced from stem explants were treated with MeJa at the concentrations of 20, 40 and 60 mg/mL for seven and fourteen days. The percentage dry weight of cultures was decreased between 3 and 5 percent from the untreated cultures. Quantitative HPLC analyses showed a significant difference in accumulation of lutein among the treatments. Lutein content was highest in microshoot cultures treated with 20 mg/mL MeJa for seven days which is 141.07 ± 19.41 µg/g dry weight. The findings showed that MeJa-elicited microshoots cultures of R. angustifolia is a potential source for lutein and a successful strategy for enhancement of lutein production in vitro has been achieved via the R. angustifolia cultures.